Prebiotic and Exercise Do Not Alter Knee Osteoarthritis in a Rat Model of Established Obesity. (December 2021) - Rios, Jaqueline Lourdes; Hart, David A.; Reimer, Raylene A.; Herzog, Walter
Objective: Metabolic disturbance is a known risk factor for cardiovascular disease and has been identified as a risk factor for the development of knee osteoarthritis. In this study, we sought to determine the effects of prebiotic fiber supplementation, aerobic exercise, and the combination of the 2 interventions, on the progression of knee osteoarthritis in a high-fat/high-sucrose diet-induced rat model of metabolic disturbance. Design: Twelve-week-old male CD-Sprague-Dawley rats were either fed a standard chow diet, or a high-fat/high-sucrose diet. After 12 weeks on diets, rats consuming the high-fat/high-sucrose diet were randomized into 4 subgroups: a sedentary, an aerobic exercise, a prebiotic fiber supplementation, and an aerobic exercise combined with prebiotic fiber supplementation group. The aerobic exercise intervention consisted of a progressive treadmill training program for 12 weeks, while the prebiotic fiber was added to the high-fat/high-sucrose diet at a dose of 10% by weight for 12 weeks. Outcome measures included knee joint damage, body mass, percent body fat, bone mineral density, insulin sensitivity, and serum lipid profile. Results: Aerobic exercise, or the combination of prebiotic fiber and aerobic exercise, improved select markers of metabolic disturbance, but not knee joint damage. However, these results need to be considered in view of the fact that the chow-fed rats had similar knee OA-like damage as the high-fat/high-sucrose–fed rats. Conclusion: Exercise or prebiotics did not increase joint damage and might be good strategies for populations with metabolic knee osteoarthritis to alleviate other health-related problems, such as diabetes or cardiovascular disorders.